Perancangan User Interface dan User Experience Aplikasi Klinik Gigi Menggunakan Metode Design Thinking - Putri Salsabila, Dhea; Pradini, Risqy Siwi; Khudori, Ahsanun Naseh (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2024)
Klinik Gigi drg. Ema Medika so far still provides services to patients manually and keeps medical records using paper documents. This causes data invalidity and sometimes the confidentiality of patient data cannot be maintained properly. To increase efficiency, this research designed an application Prototype for Klinik Gigi drg. Ema Medika. The Design Thinking method is used as an approach in Prototype development, which consists of the stages of knowing user problems and needs, identifying user problems, determining solution ideas, creating a Prototype, and conducting testing. Through the designed Prototype, users can interact with the user interface and experience the user experience. Testing was carried out using User Acceptance Testing (UAT) and produced a value of 97.37. Thus, it can be concluded that the Prototype design of the Klinik Gigi drg. Ema Medika application can meet user needs very well. The expectation is that the outcomes of this study can play a role in the adoption of information technology solutions that are both effective and efficient within the dental clinic setting, leading to an enhancement in the level of service provided to patients.